Chironomus riparius proteome responses to spinosad exposure - Monteiro, Hugo R. (2020)
The potential of proteome responses as early-warning indicators of insecticide exposure was evaluated using the non-biting midge Chironomus riparius (Meigen) as the model organism. Chironomus riparius larvae were exposed to environmentally relevant concentrations of the neurotoxic pesticide spinosad to uncover molecular events that may provide insights on the long-term individual and population level consequences. The iTRAQ labeling method was performed to quantify protein abundance changes between exposed and non-exposed organisms. Data analysis revealed a general dose-dependent decrease in the abundance of globin proteins as a result of spinosad exposure. Additionally, the downregulation of actin and a larval cuticle protein was also observed after spinosad exposure, which may be related to previously determined C. riparius life-history traits impairment and biochemical responses. Present results suggest that protein profile changes can be used as early warning biomarkers of pesticide exposure and may provide a better mechanistic interpretation of the toxic response of organisms, aiding in the assessment of the ecological effects of environmental contamination. This work also contributes to the understanding of the sublethal effects of insecticides in invertebrates and their molecular targets.